Australian Muslim responses to the discourse on terrorism in the Australian popular media - Aly, Anne (Australian Council of Social Service, 2007)
The media is often referred to as a social institution in that it is a major element of contemporary Western society. Through the media, social processes create narratives or stories within interpretative frameworks that are embedded in the cultural and political assumptions of the wider society. Since the terrorist attacks on the World Trade Centre in September 2001, the media has played a crucial role in the developing discourse on contemporary terrorism. In the Australian context, this discourse has emerged as one which implicates Australian Muslims, constructing them as a homogenous monolith with an underlying implication that Islam, and by association Australian Muslims, is secular resistant and at odds with the values of the liberal democratic state. Several textual analyses attest to the bias against Muslims in the popular Australian media discourse. However, there have been no studies into how Australian Muslims are interpreting and responding to this discourse. Based on research into the attitudes and perceptions of the media among Australian Muslims, this paper argues that the interpretation of the media discourse as defiantly anti-Muslim and the perception of the media as a powerful purveyor of public opinion has impacted on the construction of Australian Muslim identity. In responding to this discourse, Australian Muslims are creating new narratives of belonging which either reinforce or reject the underlying messages that situate them outside mainstream Australia.